2021
DOI: 10.1021/acsami.1c01452
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Droplet Vitrification Method for High-Efficiency Preservation of Rare Cells

Abstract: Cryopreservation is a key step for current translational medicine including reproductive medicine, regenerative medicine, and cell therapy. However, it is challenging to preserve rare cells for practical applications due to the difficulty in handling low numbers of cells as well as the lack of highly efficient and biocompatible preservation protocols. Here, we developed an acoustic droplet vitrification method for high-efficiency handling and preservation of rare cells. By employing an acoustic droplet ejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, this drawback does not have an impact on cryopreservation because cell solutions containing cryoprotectants are not highly viscous. This method has been applied to the cryopreservation process by Xia et al…”
Section: Droplet Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this drawback does not have an impact on cryopreservation because cell solutions containing cryoprotectants are not highly viscous. This method has been applied to the cryopreservation process by Xia et al…”
Section: Droplet Generationmentioning
confidence: 99%
“…(d) Droplets are generated by acoustic printing and dropped onto the aluminum foil. Reproduced with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Droplet Vitrificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic-droplet-based microfluidic technology has been widely used in the field of life sciences due to its high biocompatibility, label-free droplet manipulation, and ease of integration. Surface acoustic waves could be used to manipulate ultrasmall samples (∼nL) by adjusting the output frequency. In addition, the force of the acoustic waves causes minimal damage to samples (cells, proteins, and molecules), just like those widely used in fetal medical ultrasound imaging.…”
Section: Introductionmentioning
confidence: 99%
“…We also proved that the organoids prepared by this platform still retain the immune microenvironment similar to that of the parent tissue within two weeks. [44][45][46] Meanwhile, research have shown that intertumoral tumorinfiltrating lymphocytes (TILs) can directly or indirectly have a large impact on multiple antitumor immune responses and the progression of various solid tumors. [47,48] Adoptive immunotherapy with autologous tumor-infiltrating lymphocytes TIL is an attractive approach to the treatment for melanoma and renal cancer, but requires the isolation and proliferation of T cells with antitumor activity.…”
Section: Introductionmentioning
confidence: 99%